Adaptive Curriculum to Annual Syllabus Changes in Islamic Boarding Schools - Abdurahman Abdurahman; Ihdha Mar’atun Nafilah (JIEM (Journal of Islamic Education Management), 2026)
This study was motivated by the challenges faced by Islamic boarding schools in dealing with the diverse backgrounds of new students, which requires a dynamic curriculum approach. This study aims to analyze the implementation of adaptive curriculum management in response to annual syllabus changes at the I'dadiyah level of the Nurul Jadid Islamic Boarding School. The research method used was a qualitative case study with data collection techniques through in-depth interviews with informants (Coordinator, Education Division, and Teachers), classroom observation, and documentation study. The results showed that adaptive curriculum management was carried out through periodic syllabus evaluations, which were able to increase student active engagement and two-way interaction by up to 60%. The paradigm shift from theoretical to practical-functional material, particularly in the fields of Fiqh, Imla', and Pego, has been proven to reduce the cognitive load and psychological anxiety of students during the adaptation period. The conclusion of this study confirms that the professionalism of pesantren management is reflected in the flexibility of the curriculum, which is oriented towards the needs of students in order to maintain the relevance and quality of education in the modern era.